Antimicrobial Treatment of Pseudomonas aeruginosa Severe Sepsis - Johnny Zakhour; Sima L. Sharara; Joya-Rita Hindy; Sara F. Haddad; Souha S. Kanj (MDPI AG, 2022)
Pseudomonas aeruginosa is a pathogen often encountered in a healthcare setting. It has consistently ranked among the most frequent pathogens seen in nosocomial infections, particularly bloodstream and respiratory tract infections. Aside from having intrinsic resistance to many antibiotics, it rapidly acquires resistance to novel agents. Given the high mortality of pseudomonal infections generally, and pseudomonal sepsis particularly, and with the rise of resistant strains, treatment can be very challenging for the clinician. In this paper, we will review the latest evidence for the optimal treatment of P. aeruginosa sepsis caused by susceptible as well as multidrug-resistant strains including the difficult to treat pathogens. We will also discuss the mode of drug infusion, indications for combination therapy, along with the proper dosing and duration of treatment for various conditions with a brief discussion of the use of non-antimicrobial agents.